Teen Binge Drinking - Suzanna Smith (EDIS, 2012)
“Raising teenagers is a tough job. I know I’m not the only mom who worries about the challenges our children face, including the issue of teenage drinking. There are many reasons to be concerned: Youth who use alcohol are at greater risk for unprotected sexual intercourse, coerced sexual activity, use of marijuana, and poor academic performance.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, August 2012.